Comparative study of selected subcarrier index modulation OFDM schemes - Rawaa J. Hasan; Hikmat N. Abdullah (Universitas Ahmad Dahlan, 2019)
Orthogonal frequency division multiplexing with subcarrier index modulation (SIM-OFDM) is recently proposed to enhance the performance of traditional OFDM. By incorporating the index modulation in OFDM, the data can be sent on the indices of subcarriers as well as the subcarriers themselves reducing the system complexity. In addition, the Peak to Average Power Ratio (PAPR) and Inter Carrier Interference (ICI) can be reduced by switching on /off some OFDM subcarriers in OOK fashion. In this paper, a comparative study of OFDM with SIM_OFDM and Enhanced SIM_OFDM methods in terms of complexity, spectral efficiency and bit error rate over AWGN channel using two power policies is presented. The simulation results showed that at bit error rate of 10-3, SIM_OFDM and ESIM_OFDM achieved gains in Eb/No of 1.1 dB and 2 dB over 4-QAM OFDM respectively under power reallocation policy. However, the results also showed that traditional OFDM has better spectral efficiency compared to both SIM_OFDM and ESIM_OFDM especially at high M-ary orders.